Water Sanitation and Hygiene (WASH): Merits and Demerits in schools - SARKINGOBIR, YUSUF (Surabaya Biomedical Journal, 2025)
This study explores the merits and demerits of Water Sanitation and Hygiene (WASH) in schools. WASH is crucial for maintaining health and preventing diseases in educational settings. The study highlights the importance of providing sufficient and safe water, basic sanitation, and hygiene facilities in schools. It also discusses the effects of poor WASH on education, including the spread of diseases, poor academic performance, and absenteeism. The study suggests improvements in WASH infrastructure, health education, and community involvement to promote healthy behaviors and environments in schools.